Pengaruh Penggunaan Game Online terhadap Interaksi Sosial Remaja di Sekolah SMA Triguna Utama Ciputat - Fiki, Fiki; Ati Kusmawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The people living in today's era are inseparable from the internet. Since the emergence of the internet with adequate access, various aspects of community life have changed drastically and dramatically. This phenomenon is often seen especially among students and teenagers, greatly influencing the social interaction process, resulting in a tendency to play online games significantly. This research discusses the influence of social interaction among adolescent users of online games at Triguna Utama Ciputat High School. The research problem formulation is first, whether there is an influence of online game addiction on adolescent behavior at Triguna Utama Ciputat High School. Second, whether there is an influence of student social interaction on students addicted to online games at Triguna Utama Ciputat High School. The aim is to determine the influence of online game addiction on adolescent behavior at Triguna Utama Ciputat High School, and secondly, to determine the influence of social interaction on students addicted to playing online games at Triguna Utama Ciputat High School. The method used in this research is qualitative method. The result of this study show that use of online game affect teenagers social interactions through action using symbols, meaning, and cues.